2005
DOI: 10.3171/ped.2005.102.3.0288
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome of lesionectomy in glioneuronal tumors associated with epilepsy in children

Abstract: The results of this study indicate that lesionectomy may provide good long-term seizure control in the majority of children with epileptogenic glioneuronal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 51 publications
(117 reference statements)
3
60
0
Order By: Relevance
“…39,40,68 Therefore, considering the good prognosis for epilepsy and the possible, although low, risk of malignant transformation, we think that ELGTs should be properly and quickly diagnosed by adequate imaging investigations and considered early for surgical treatment, particularly in young patients, to avoid psychosocial consequences and disability due to long-standing medically intractable seizures. 23,31,33,34,41,42,44,45,76,99 In our group of 17 patients with isolated FCD, we identified FCD Type IIa in 11 patients, FCD Type Ic in 6 patients. Of the patients with FCD Type IIa, 8 (72.7%) had Class I outcomes, 7 of them (63.6% of the FCD IIa group) had Class IA, whereas considering FCD Type Ic, (Engel Class I outcome was observed in 2 (33.3%) of 6 patients, with only 1 patient (16.6%) having a Class IA outcome.…”
Section: Discussionmentioning
confidence: 92%
“…39,40,68 Therefore, considering the good prognosis for epilepsy and the possible, although low, risk of malignant transformation, we think that ELGTs should be properly and quickly diagnosed by adequate imaging investigations and considered early for surgical treatment, particularly in young patients, to avoid psychosocial consequences and disability due to long-standing medically intractable seizures. 23,31,33,34,41,42,44,45,76,99 In our group of 17 patients with isolated FCD, we identified FCD Type IIa in 11 patients, FCD Type Ic in 6 patients. Of the patients with FCD Type IIa, 8 (72.7%) had Class I outcomes, 7 of them (63.6% of the FCD IIa group) had Class IA, whereas considering FCD Type Ic, (Engel Class I outcome was observed in 2 (33.3%) of 6 patients, with only 1 patient (16.6%) having a Class IA outcome.…”
Section: Discussionmentioning
confidence: 92%
“…Although some authors reported that good seizure control can be obtained despite incomplete tumor resection, 11,12 the importance of total tumor removal for seizure control has been emphasized by many authors, especially in recent studies. 4,5,13 However, Daumas-Duport et al 14 reported…”
Section: 10mentioning
confidence: 99%
“…Long-term clinical follow-up typically shows no evidence of recurrence, even in patients with incomplete surgical resection ( 76,97,99,102,107,126). Risk factors for post operative recurrent seizures at long-term follow-up include longer pre-operative history of seizures, cortical dysplasia next to DNT and residual tumour ( 85,100,127,128). Malignant transformation is extremely rare, only 2 cases reported from 700 cases of DNTs (129).…”
Section: Prognostic Factorsmentioning
confidence: 99%